Pyridoxamine and Aminoguanidine Attenuate the Abnormal Aggregation of β-Tubulin and Suppression of Neurite Outgrowth by Glyceraldehyde-Derived Toxic Advanced Glycation End-Products - Ooi, Hayahide; Nasu, Ryuto; Furukawa, Ayako; Takeuchi, Masayoshi; Koriyama, Yoshiki (Frontiers in Pharmacology, 2022)
Diabetes mellitus (DM) has been identified as a risk factor for the onset and progression of Alzheimer’s disease (AD). In our previous study, we demonstrated that glyceraldehyde (GA)-derived toxic advanced glycation end-products (toxic AGEs, TAGE) induced similar alterations to those observed in AD. GA induced dysfunctional neurite outgrowth via TAGE-β-tubulin aggregation, which resulted in the TAGE-dependent abnormal aggregation of β-tubulin and tau phosphorylation in human neuroblastoma SH-SY5Y cells. However, the effects of inhibitors of AGE formation on dysfunctional neurite outgrowth caused by GA-induced abnormalities in the aggregation of β-tubulin and tau phosphorylation remain unknown. Aminoguanidine (AG), an AGE inhibitor, and pyridoxamine (PM), a natural form of vitamin B6 (VB6), are effective AGE inhibitors. Therefore, the present study investigated whether AG or PM ameliorate TAGE-β-tubulin aggregation and the suppression of neurite outgrowth by GA. The results obtained showed that AG and PM inhibited the formation of TAGE-β-tubulin, mitigated the GA-induced suppression of neurite outgrowth, and reduced GA-mediated increases in tau phosphorylation levels. Collectively, these results suggest the potential of AG and PM to prevent the DM-associated onset and progression of AD.